Pattern of intrauterine growth retardation among low birth weight neonates (BIRDEM Medical Journal, 2022)
Background: There is an association between intrauterine growth retardation (IUGR) and subsequent development of diabetes mellitus, coronary artery disease and hypertension during adult life. With this context, it is vital to give attention about the patterns of body proportion of IUGR babies. The aim of this study was to determine the proportion of asymmetric distribution IUGR in contrast to symmetric distribution among babies with low birth weight (LBW).Methods: This cross-sectional study was conducted in the Department of Pediatrics, Sher-e-Bangla Medical College, Barisal,from January 2012 to June 2012, with a total 114 babies with LBW. All singleton newborns, within 24 hours of birth, having birth weight < 2.5 kg was were included. Weight was plotted in weight for gestation age centile chart. Then Ponderal index (PI) was calculated to determine asymmetric and symmetric IUGR by using the formula. Convenient sampling was used. Data were analyzed with SPSS. P value